1992
DOI: 10.1007/bf01605986
|View full text |Cite
|
Sign up to set email alerts
|

Immunocytochemistry in adrenocortical tumours: A clinicomorphological study of 72 neoplasms

Abstract: Surgical specimens of 72 adrenocortical tumours (ACTs) were investigated. Histologically, 57 tumours were classified as adenomas and 15 as carcinomas. In 9 of the latter cases, distant metastases and/or lethal outcome of disease was recorded. Immunocyto-chemistry showed only 2 ACTs to be positive for cytokeratin and 6 for vimentin. None of the 72 tumours showed argyrophilia or immunoreactivity for epithelial membrane antigen (EMA), S-100 protein, chromogranin A, Leu 7 or Leu-M1, while 31 cases exhibited positi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
1
1

Year Published

1993
1993
2016
2016

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(27 citation statements)
references
References 20 publications
3
22
1
1
Order By: Relevance
“…The monoclonal antibody D11, was introduced as a marker for adrenal cortical neoplasms by Schroder et al [27]. The antibody recognizes several 59 kD proteins capable of binding apolipoprotein E. Schroder et al demonstrated nuclear positivity in 100% of benign (57 cases) and malignant (15 cases) adrenocortical tumors [27].…”
Section: Monoclonal Antibody D11mentioning
confidence: 99%
See 2 more Smart Citations
“…The monoclonal antibody D11, was introduced as a marker for adrenal cortical neoplasms by Schroder et al [27]. The antibody recognizes several 59 kD proteins capable of binding apolipoprotein E. Schroder et al demonstrated nuclear positivity in 100% of benign (57 cases) and malignant (15 cases) adrenocortical tumors [27].…”
Section: Monoclonal Antibody D11mentioning
confidence: 99%
“…The antibody recognizes several 59 kD proteins capable of binding apolipoprotein E. Schroder et al demonstrated nuclear positivity in 100% of benign (57 cases) and malignant (15 cases) adrenocortical tumors [27]. A subsequent study by Tartour et al demonstrated nuclear positivity in 44% (8 of 18 cases) of carcinomas, all of which were well differentiated [29].…”
Section: Monoclonal Antibody D11mentioning
confidence: 99%
See 1 more Smart Citation
“…Although protein expression of epidermal growth factors, p53, transforming growth factor ␣, and P-glycoprotein, may be useful in distinguishing benign adenomas from malignant adrenocortical carcinomas, none of these markers has been shown to be an independent prognostic factor for survival rates in patients with an adrenocortical carcinoma. [13][14][15][16] We demonstrated that tumor size (Ͼ12 cm), the number of mitotic figures (Ն6 per 10 high-power fields), and intratumoral hemorrhage can predict a lower survival rate in patients undergoing curative resection for adrenocortical carcinoma. The presence of tumor necrosis nearly reached significance (P=.06), and with additional numbers, may also be an independent predictor.…”
Section: Methodsmentioning
confidence: 99%
“…The differential diagnosis between adrenal carcinoma and adenoma is mainly made by the rate of mitotic cells. The cut-off line is usually 5 mitoses per 50 high power fields (15). Moreover, anaplastic seminoma is also defined by the mitotic rate, which is more than thirty mitoses in a total of 10 high power fields (13).…”
Section: Discussionmentioning
confidence: 99%